Yona of the dawn. 24 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2020)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-Won. But everything changes on her 16th birthday when tragedy strikes her family!... In order to prevent war with the nation of Xing, Yona and Hak ask the informant Ogi to deliver an important letter to Su-won. Later, Yona races to the Fire Tribe to appeal to an ally there -- Kang Tae-jun! WIll Yona succeed in helping her friends who are captured in Xing?"--Provided by publisher.